2009
DOI: 10.1287/orsc.1090.0426
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Organizational Ambidexterity: Dimensions, Contingencies, and Synergistic Effects

Abstract: Significant ambiguity remains in the literature regarding the conceptualization of organizational ambidexterity. We unpack this construct into one with two dimensions we term the balance dimension of ambidexterity (BD) and the combined dimension of ambidexterity (CD). BD corresponds to a firm's orientation to maintain a close relative balance between exploratory and exploitative activities, whereas CD corresponds to their combined magnitude. We reason that these dimensions are conceptually distinct, and rely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

62
1,544
9
22

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,121 publications
(1,761 citation statements)
references
References 76 publications
62
1,544
9
22
Order By: Relevance
“…(Levinthal & March, 1993), one of the goals of exploration is to find new alternatives to improve current ones (March, 1991). We can thus affirm that strategic behaviours1 seek new ways to adapt to the environment (Cao et al, 2009) and different possibilities for improving organizations' production. One of the firm's options for adapting and improving the production process is to search for knowledge, whether through entrepreneurial innovation or through the reorientation of its own abilities.…”
Section: Exploration and Exploitation Strategies And Manufacturing Flmentioning
confidence: 86%
See 1 more Smart Citation
“…(Levinthal & March, 1993), one of the goals of exploration is to find new alternatives to improve current ones (March, 1991). We can thus affirm that strategic behaviours1 seek new ways to adapt to the environment (Cao et al, 2009) and different possibilities for improving organizations' production. One of the firm's options for adapting and improving the production process is to search for knowledge, whether through entrepreneurial innovation or through the reorientation of its own abilities.…”
Section: Exploration and Exploitation Strategies And Manufacturing Flmentioning
confidence: 86%
“…Jansen, Van Den Bosch, and Volberda (2006) suggest that developing both behaviours permits the firm to improve its performance in dynamic environments. Cao, Gedajlovic, and Zhang (2009), as well, observed that a close balance of exploitation and exploration is more important for performance in smaller firms, because of the accessible resources available, than in larger firms, which have access to sufficient internal or externally located resources.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration competencies, in contrast, are associated with more radical innovations, as their focus is on the emergence of new customers and market needs (Cao et al, 2009;Danneels, 2002), suggesting that exploratory innovation requires non-routine problem solving and a deviation from existing knowledge (Jansen et al, 2006).…”
Section: Sustainability Exploration and Sustainability Exploitation: mentioning
confidence: 99%
“…The capacity of an organisation to pursue high levels of exploration and exploitation simultaneously has been referred to as ambidexterity (Cao et al, 2009). Nonetheless, the literature supports a positive relationship between exploration and exploitation strategies and organisational performance.…”
Section: Sustainability Exploration and Sustainability Exploitation: mentioning
confidence: 99%
“…Las organizaciones ambidiestras son capaces de desarrollar tanto la explotación como la exploración; explotan los conocimientos que poseen, manteniéndose abiertas a la exploración de conocimientos y oportunidades nuevas (López Zapata, García Muiña, & García Moreno, 2012). Las empresas buscan alcanzar y mantener dicha ambidiestría pues su consecución se asocia con los resultados a corto plazo y la supervivencia a largo plazo (Cao, Gedajlovic, & Zhang, 2009). A pesar de su importancia para el éxito de las empresas, no es fácil ni sencillo ser ambidiestro.…”
Section: Introductionunclassified